2019
DOI: 10.1038/s41598-019-50712-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dichromatism and color diversity in the spiny lava lizard Tropidurus spinulosus using lizard visual modelling

Abstract: Colors are important vehicles for social signals in many taxa. In Squamata, previous studies have linked color characteristics and chromatic diversity to sexual selection and, particularly, species showing male-biased body size dimorphism also showed male-biased dichromatism and color diversity. Sexual dichromatism may occur in body regions used for conspecific communication and it may be expressed at wavelengths, such as ultraviolet, easily perceivable by conspecifics. We tested this prediction in a social li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…This phenomenon which is known as sexual dichromatism where one sex is distinctly or brightly coloured than the other is widespread in the animal kingdom and is well known from fish (Kingston et al, 2003), lizards (Barry Sinervo & Lively, 1996; M Olsson et al, 2007; Sacchi et al, 2013; James E Paterson & Blouin-demers, 2017) and birds (Burns & Shultz, 2012). One of the most well known underlying causes for sexual dichromatism is female mate preference to certain colour morphs (Stuart-Fox & Ord, 2004; Chen et al, 2012; Rossi et al, 2019). However, L. fallax is not only sexually dichromatic, the males also show throat colour polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon which is known as sexual dichromatism where one sex is distinctly or brightly coloured than the other is widespread in the animal kingdom and is well known from fish (Kingston et al, 2003), lizards (Barry Sinervo & Lively, 1996; M Olsson et al, 2007; Sacchi et al, 2013; James E Paterson & Blouin-demers, 2017) and birds (Burns & Shultz, 2012). One of the most well known underlying causes for sexual dichromatism is female mate preference to certain colour morphs (Stuart-Fox & Ord, 2004; Chen et al, 2012; Rossi et al, 2019). However, L. fallax is not only sexually dichromatic, the males also show throat colour polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Male colour polymorphism is also known to be strongly influenced by sexual selection (Healey et al, 2007; Wellenreuther et al, 2014). Previous studies have shown that females show a higher preference to a particular male colour morph when there are multiple colour morphs among males in the population (Kingston et al, 2003; Stuart-Fox & Ord, 2004; Healey et al, 2007; Rossi et al, 2019). Interestingly, it has also been shown that male throat colour polymorphism is related to habitat selection in tree lizards (J. E. Paterson & Blouin-Demers, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…body size, as occurs in Tropidurus spinulosus ( López Juri et al, 2020 ). Moreover, trade-offs between colour ornamentation variability ( Rossi et al, 2019 ) and sperm resistance to oxidative stress activated by increased temperature ( Tomášek et al, 2017 ) might also produce variation in sperm velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Study species: Tropidurus spinulosus is a member of the Tropiduridae family, which includes many social lizard species [67]. In particular, in T. spinulosus individuals are often observed in groups on rocky outcrops, interacting with one another [49]. It shows a narrow range of preferred temperatures: selected temperature (Tsel) = 33.7˚C, first quartile of the preferred range (Tset-min) = 32.2 and third quartile of the preferred range (Tset-max) = 35.2 [68].…”
Section: Methodsmentioning
confidence: 99%
“…Lizards are an interesting model to study social interactions in warming environments [42] because they are ectotherms and exhibit a marked social behaviour and interesting sexual selection dynamics [43,44]. Males may move between perch positions to attract females and repel other males [45][46][47], and may engage in behavioural displays to communicate with conspecifics [48][49][50]. Female and male mate choice has been reported in lizards and is often based on visual phenotypic traits [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%